PENGARUH PEMBERIAN SWEITENIA MAHAGONI L. TERHADAP PENURUNAN KOLESTEROL PADA WANITA MENOPAUSE - Stephani Pratiwi Sorongan; Bela Purnama Dewi (Jurnal Kesehatan dan Pembangunan, 2026)
Most menopausal women experience an increase in cholesterol levels due to a decrease in body function, one of which is a decrease in hormones. This study aims to determine the effect of administering Sweitenia Mahagoni L on reducing cholesterol in menopausal women. This research method uses a pre-experimental research method with a one group pretest—post test design. The sample in this study was menstruating mothers with cholesterol levels >200 mg/dl. The sample was 32 samples using the purposive sampling method. The research was conducted on January 9 - March 9 2025 at the Sekip Palembang Community Health Center. The results of this study showed that based on the Wilcoxon test, it was 0.001 < 0.05, so it could be concluded that there was a significant effect of giving Sweitenia Mahagoni L on reducing cholesterol levels in menopausal women. It is hoped that this research will be useful for menopausal mothers with hypercholerolemia and can be consumed at home as an alternative non-pharmacological treatment.